Optimalisasi Penatalaksanaan Kegawatan di Ruang Kegawatdaruratan pada Era New Normal - Yarwin Yari; Veronica Yeni Rahmawati; Ernawati Ernawati; Fendy Yesayas; Ayu Lestari; Arizton Putra Jaya; Eni Fatma Sari (PT.Mantaya Idea Batara, 2021)
Abstract: Since COVID-19 was first discovered in Wuhan, it has caused COVID-19 referral hospitals to be